The quality of pathological reports of postoperative specimens in rectal cancer: an audit from the Mazovia region - Olszyna-Serementa, Marta; Kołodziejczyk, Milena; Sprawka, Arkadiusz; Nasierowska-Guttmejer, Anna; Bujko, Krzysztof (Polish Journal of Pathology, 2009)
Background: Recently, pathologists have recommended new standards of post operative specimen evaluation in rectal cancer. These new standards include: macroscopic assessment of the quality of surgical excision of mesorectum, microscopic measurement of circumferential resection margin and the assessment of at least 12 mesorectal lymph nodes regarding the presence of metastases. The purpose of our study was to find out whether those standards have been implemented into a routine practice in Poland. Material and methods: This is a retrospective evaluation of pathological reports of postoperative specimens in 51 consecutive rectal cancer patients who were referred to our institution from 19 hospitals for postoperative chemoradiation between January 2006 and December 2007. Items were audited in pathological reports that were mentioned in the background. Results: Only 14% of pathological reports included the macroscopic assessment of the quality of surgical excision of mesorectum and 57% reported microscopic measurement of circumferential resection margin. The median number of retrieved lymph nodes was 9, with a range between 0 and 36. Conclusion: The quality of pathological reports was unsatisfactory. Actions should be taken on a national level to improve the current situation. There is an urgent need for providing pathologists with adequate guidelines.